Modelling and simulation of residual stress of strip during continuous annealing process. Issue 2 (27th August 2019) - Su, Chun-Jian; Li, Yong; Yang, De-Xing; Bai, Zhen-Hua; Wang, Rui; Lv, Yu-Ting; Duan, Jian-Gao
Abstract : Purpose: The purpose of this study is to solve the key problem of the residual stress of strip in buckling and deviation during the continuous annealing process (CAP). Design/methodology/approach: Considering the one-to-one correspondence between deformation and residual stress, the strip was divided into multiple elements. To obtain the total deformation of each element, the influence model of some factors on the deformation of steel strip element was established. Then, according to the constitutive equation of residual stress and deformation, and the deformation coordination relation between strip elements, a set of calculation model, which is suitable for residual stress of strip during CAP was established, the model precision was verified by finite element method simulation, and the influences on residual stress of strip were also analyzed. Findings: The weighted calculation of comparison between analytical results and simulation shows that the accuracy of the analytical method is within 10 per cent, which fully meets the requirements. Originality/value: The different residual stress of steel strip can be displayed quickly and intuitively in the synchronous process segment according to this model, which is of great importance to the prevention of strip buckling and deviation.